1961
DOI: 10.1084/jem.114.3.363
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Opsonins in the Clearance of Living and Inert Particles by Cells of the Reticuloendothelial System

Abstract: An investigation of the clearance of bacteria and colloids from the blood stream of mice has shown that both living and inert particles require serum factors (opsonins) in order that they may be phagocytosed by the macrophages of the reticuloendothelial system. It has been demonstrated that after the injection of a large dose of colloid there is a depletion of these serum opsonins which appears to account for the reduced rate of clearance of a second dose of colloid or living bacteria, since replacement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

1963
1963
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(49 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…When the above evidence is considered in conjunction with the low efficiency of serum from tolerant donors in neutralizing endotoxin toxicity despite in vitro incubation at 37 ° C for 1 hour (21), it appears likely that the humoral factors responsible for tolerance act, in part at least, indirectly by preparing endotoxin for more rapid phagocytosis by the RES; i.e., they behave as opsonins. This thesis is consistent with the hypothesis of Jenkin and Rowley (22) that opsonins are required for RES phagocytosis of colloidal particles. It seems peculiar that such "opsonins" are resistant to thorotrast, since RES blockade with colloidal agents is accompanied by opsonin depletion (22): Recent findings by Murray (23) resolve this problem.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When the above evidence is considered in conjunction with the low efficiency of serum from tolerant donors in neutralizing endotoxin toxicity despite in vitro incubation at 37 ° C for 1 hour (21), it appears likely that the humoral factors responsible for tolerance act, in part at least, indirectly by preparing endotoxin for more rapid phagocytosis by the RES; i.e., they behave as opsonins. This thesis is consistent with the hypothesis of Jenkin and Rowley (22) that opsonins are required for RES phagocytosis of colloidal particles. It seems peculiar that such "opsonins" are resistant to thorotrast, since RES blockade with colloidal agents is accompanied by opsonin depletion (22): Recent findings by Murray (23) resolve this problem.…”
Section: Discussionsupporting
confidence: 91%
“…This thesis is consistent with the hypothesis of Jenkin and Rowley (22) that opsonins are required for RES phagocytosis of colloidal particles. It seems peculiar that such "opsonins" are resistant to thorotrast, since RES blockade with colloidal agents is accompanied by opsonin depletion (22): Recent findings by Murray (23) resolve this problem. It was shown that opsonins possess specificity determined by the surface properties of the colloidal particle.…”
Section: Discussionsupporting
confidence: 91%
“…Freedman (27), who has done extensive work in this area, does not attribute these significant observations to the presence of antibodies; the results, however, are consistent with an immunological mechanism. The factors involved could be the same as the opsonins, unrelated to O antibodies, which assist the RES in the destruction of certain Gram-negative bacteria (29). Jenkin and Rowley reported that such opsonins are removed non-specifically from the serum by colloidal carbon.…”
Section: Discussionmentioning
confidence: 99%
“…The depressed rate of carbon elearanee which followed 1 and 2 doses of ALS is probably due largely to a limited availability of serum opsonins whieh are essential for the phagoeytosis of carbon particles (Jenkin and Rowley, 1961;Normann and Benditt, 1965;Filkins and Diluzio, 1966). The necessity for phagoeytic eells to dispose of large amounts of heterologous protein and damaged or opsonized cells would result in a temporary depletion of opsonins and thereby severely limit the eapaeity of macrophage.s to carry out additional phagoeytosis of carbon particles.…”
Section: Discussionmentioning
confidence: 99%